AYAH PERMISIF MENINGKATKAN RISIKO ANAK UNTUK MEROKOK - Husna, Fadilahtul; Hastuti, Dwi (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2015)
Today, the problems of adolescent especially in smoking preference in Indonesia is very alarming. This study was conducted to analyze the influence of fathering on smoking behavior of junior high school students in rural area of Bogor. The design of this research was cross sectional study and used survey method. This study involved 60 students of seventh and eighth grades in two junior high schools in the Pamijahan Sub District, Bogor District, West Java Province that were selected by proportional random sampling. Data collection was conductedby self-administered and analyzed by independent samples t-test, Pearson’s correlation test, Chi-Square test, and logistic regression test. Fathering was measured base on parenting styles and modelling. Parenting style (authoritarian and permissive) correlated significantly with smoking behavior of students, whereas modelling didn’t correlate between male and female student. Age of student, sex of student, and father’s parenting style (authoritative and permissive) correlated significantly with student’s smoking behavior. Smoking behavior of students was influenced by length of father’s education and parenting styles (authoritative and permissive). Increasing of father’s education and using authoritative parenting style can decrease risk of student’s smokingbehavior, while the permissive parenting style of father can increase risk of student’s smoking behavior.